2019
DOI: 10.14710/jtsiskom.7.1.2019.38-46
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Call Drops in GSM Network using Artificial Neural Network

Abstract: Global System for Mobile communication is a digital mobile system that is widely used in the world. Over the years, the number of subscribers has tremendously increased, the quality of service (Call Drop Rate) became an issue to consider as many subscribers were not satisfied with the services rendered. In this paper, we present the Artificial Neural Network approach to predict call drop during an initiated call. GSM parameters data for the prediction were acquired using TEMS Investigations software. The measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Hence, one of the objectives of the study was to determine the call-drop probability distribution of the wireless cellular network. The result has indicated that the call-drop rates of the four major networks (MTN, Vodafone, Airtel-Tigo, and Glo) in the country have different probability distributions, confirming the findings of other authors that call-drops have different probability distributions (Aalo & Efthymoglou, 2010;Boggia et al, 2005;Boggia et al,2007;Fang et al, 1997;Pattaramalai et al, 2007;Erunkulu et al,2019;Ojuh & Isabona, 2021;Patil, 2016), and that the probability distribution of call-drop is inconclusive (Erunkulu et al, 2019;Tarkaa & Mom, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…Hence, one of the objectives of the study was to determine the call-drop probability distribution of the wireless cellular network. The result has indicated that the call-drop rates of the four major networks (MTN, Vodafone, Airtel-Tigo, and Glo) in the country have different probability distributions, confirming the findings of other authors that call-drops have different probability distributions (Aalo & Efthymoglou, 2010;Boggia et al, 2005;Boggia et al,2007;Fang et al, 1997;Pattaramalai et al, 2007;Erunkulu et al,2019;Ojuh & Isabona, 2021;Patil, 2016), and that the probability distribution of call-drop is inconclusive (Erunkulu et al, 2019;Tarkaa & Mom, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…The ordinary least squares model is used to lessen the loss of factor for the provided set of training samples: as shown in ( 8): (8) where pi represents the training set, qi is the vector, and denotes the variance of estimate. The following model is used to illustrate the reduction in cost consumption and squared error values through ridge regression as shown in ( 9): (9) where  represents the regularization parameter,  indicates the regularization parameter, which is used to reduce the estimate variance by balancing the tradeoff among the bias and variance. To find the best parameters for lowering the error values, cross validation is also carried out in this model.…”
Section: Linear Kernel Regression Model (Lkrm)mentioning
confidence: 99%
“…networks are a technique that makes complex networks simpler and guarantees better service. A major factor in it is Machine Learning (ML) [9], which is a subset of artificial intelligence that helps to comprehend actions and see patterns beyond human recognition, repairs the holes left by human limitations. ML allows technologies to improve the learning capacity without having to be explicitly programmed for performing particular tasks [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Call drop occurs when a call is terminated before the speaking parties have ended their conversational tone and one of them has hung up. The percentage of total calls is a common way to describe this (Tarkaa & Mom, 2018;Erunkulu et al, 2019). A telephone conversation may be cancelled before the parties who initiated the call choose to do so because of a technical issue.…”
Section: Call-drop In Mobile Cellular Networkmentioning
confidence: 99%